2022
DOI: 10.1111/ced.15157
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic drug monitoring in dermatology: the way towards dose optimization of secukinumab in chronic plaque psoriasis

Abstract: Summary Background Despite the favourable efficacy profile of secukinumab, clinicians encounter varying clinical responses among patients potentially associated with under‐ and overdosing. As biologics are expensive, their rational use is crucial and evident. Therapeutic drug monitoring could guide clinicians in making decisions about treatment modifications. Aim In this multicentre, prospective study, we aimed to develop and validate a secukinumab immunoassay and searched for the therapeutic window in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 52 publications
(99 reference statements)
0
6
0
Order By: Relevance
“…Aiming to develop a TDM strategy for secukinumab in psoriasis, Soenen et al . confirmed the secukinumab underexposure in real‐world overweight patients and determined a minimal effective secukinumab threshold of 39·1 mg L –1 associated with achieving PASI ≤ 2 or ΔPASI ≥ 90% 9 …”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Aiming to develop a TDM strategy for secukinumab in psoriasis, Soenen et al . confirmed the secukinumab underexposure in real‐world overweight patients and determined a minimal effective secukinumab threshold of 39·1 mg L –1 associated with achieving PASI ≤ 2 or ΔPASI ≥ 90% 9 …”
mentioning
confidence: 73%
“…8 Aiming to develop a TDM strategy for secukinumab in psoriasis, Soenen et al confirmed the secukinumab underexposure in real-world overweight patients and determined a minimal effective secukinumab threshold of 39Á1 mg L -1 associated with achieving PASI ≤ 2 or DPASI ≥ 90%. 9 This trial provides high-quality evidence to support above-label dosing of secukinumab to improve treatment outcomes in an otherwise difficult-to-treat patient population. Notwithstanding the importance of these findings in optimizing dosing in overweight patients, the need for interventions for sustainable weight-reduction-directed lifestyle behaviour in this patient group should be emphasizednot merely to improve treatment outcomes, but rather as an opportunity to optimize psoriasis-related comorbidities and patients' overall health status.…”
mentioning
confidence: 94%
“…Serum was prepared and stored at a minimum of 20°C until C t analysis in the Laboratory of Diagnostic and Therapeutic Antibodies, KU Leuven. C t s for SEC were measured as described previously 40 . C t s for IXE were determined by use of an in‐house‐developed, sandwich‐type enzyme‐linked immunosorbent assay.…”
Section: Methodsmentioning
confidence: 99%
“…C t s for SEC were measured as described previously. 40 C t s for IXE were determined by use of an in-housedeveloped, sandwich-type enzyme-linked immunosorbent assay. In the assay, IXE is captured between MA-IXE117E12 as coating antibody and biotinylated MA-IXE100F5 as detecting antibody, allowing quantification of IXE concentrations ranging from 0.5 to 80.0 μg/ml.…”
Section: Blood Sampling and C T Measurementmentioning
confidence: 99%
“…10 Evidence favouring TDM of biologics in psoriasis is rising. [11][12][13][14][15] In order to implement TDM, a well-defined exposure-response relationship must be present.…”
Section: Introductionmentioning
confidence: 99%